Development of Experimental Digital Comics to Stimulate Kindergarteners’ Science Process Skills - Fatwini; I Gede Astawan; Gede Wira Bayu (Jurnal Penelitian Pendidikan IPA, 2025)
Science process skills play a vital role in the cognitive and scientific development of early childhood learners. However, learning media specifically designed to cultivate these skills, particularly those that are digital and incorporate experimental components are still limited in availability. This study aims to develop digital comic-based learning media through experiments to stimulate science process skills in kindergarten children aged 5-6 years at PAUD 3 Serangkai, West Lombok. The development model used is ADDIE, which includes the stages of analysis, design, development, implementation, and evaluation. Data were collected through material and media expert validation, small group trials, field trials, observations, and pretest-posttest of children's science process skills. The validation results show that this media is highly valid, with an average score of over 95% for both material and media design. The field trials, involving 36 children and two teachers, indicated that the media is very practical to use and successfully attracts interest and encourages active participation from the students in the learning processThe results of statistical analysis using the Paired Sample t-Test showed that the significance value (Sig. 2-tailed) was 0.000 < 0.05, indicating a statistically significant improvement in children's science process skills after using the media, particularly in the abilities to observe, classify, predict, measure, and communicate. This digital comic-based learning media through experiments effectively integrates engaging visuals with real experimental activities, providing a fun and meaningful learning experience. Therefore, this media is valid, practical, and effective as an innovative learning resource in early childhood education to optimally stimulate science process skills.